2021
DOI: 10.1021/acs.chemrestox.0c00409
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Responses of α-Pinene-Derived Secondary Organic Aerosol and Its Molecular Tracers in Human Lung Cell Lines

Abstract: Secondary organic aerosol (SOA) is a major component of airborne fine particulate matter (PM 2.5 ) that contributes to adverse human health effects upon inhalation. Atmospheric ozonolysis of α-pinene, an abundantly emitted monoterpene from terrestrial vegetation, leads to significant global SOA formation; however, its impact on pulmonary pathophysiology remains uncertain. In this study, we quantified an increasing concentration response of three well-established α-pinene SOA tracers (pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 88 publications
1
51
0
Order By: Relevance
“…The oxidation products of α-pinene are widely seen in the atmosphere and have shown to readily form in the presence of typical atmospheric oxidants. ,,, However, their formation in the presence of gas-phase NO 2 and in the absence of other oxidizers such as O 3 and HO • was not previously observed. Therefore, it is proposed that the α-pinene oxidation by NO 2 can occur in the presence of mineral surfaces, thereby producing the observed oxidation products of α-pinene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The oxidation products of α-pinene are widely seen in the atmosphere and have shown to readily form in the presence of typical atmospheric oxidants. ,,, However, their formation in the presence of gas-phase NO 2 and in the absence of other oxidizers such as O 3 and HO • was not previously observed. Therefore, it is proposed that the α-pinene oxidation by NO 2 can occur in the presence of mineral surfaces, thereby producing the observed oxidation products of α-pinene.…”
Section: Resultsmentioning
confidence: 99%
“… 24 In addition, reactions of α-pinene with atmospheric oxidizers, such as O 3 and OH radicals lead to the formation of a range of α-pinene oxidation products that are known as first generation oxidation products. 4 , 6 , 25 , 26 Several of these products have been identified as pinonaldehyde, pinonic acid, and α-pinene oxide, as well as a structurally diverse set of organic peroxides. These oxidation products can also act as a reactant in generating atmospheric ON compounds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of cell culture studies reported the capacity of SOA to induce cell toxicity. ,,,,,, Moreover, it has also been reported that SOA have the capacity to alter transcriptomic profiles of lungs cells (e.g., upregulation of tumor protein 53 (p53) signaling pathway). , The latter, known as the guardian of the genome, regulates various processes in response to stress detection. Indeed, p53-targeted genes can induce cell cycle arrest, apoptosis, or autophagy in a dependent manner of SOA.…”
Section: Pathogenic Impact Of Soamentioning
confidence: 99%